A comparison of SSM/I‐derived global marine surface‐specific humidity datasets. (30th September 2014) - Prytherch, John; Kent, Elizabeth C.; Fangohr, Susanne; Berry, David I.
ABSTRACT Satellite‐based microwave sensors have, since the 1980s, provided a means to retrieve near‐surface marine specific humidity (qa), accurate estimation of which is necessary for climate and air–sea interaction applications. Seven satellite measurement‐derived monthly mean humidity datasets are compared with one another and with a dataset constructed from in situ measurements. The means, spatial and temporal structures of the datasets are shown to be markedly different, with a range of yearly, global mean qa of ∼1 g kg–1. Comparison of the datasets derived using the same satellite measurements of brightness temperature reveals differences in qa that depend on the source of satellite data; the processing and quality control applied to the data; and the algorithm used to derive qa from the satellite measurements of brightness temperature. Regional differences between satellite‐derived qa due to the choice of input data, quality control and retrieval algorithm can all exceed the accuracy requirements for surface flux calculation of ∼0.3 g kg–1 and in some cases can be several g kg–1 in monthly means for some periods and regions.